Understanding the Growth in Welfare Benefit Receipt in Britain: A Review of the Evidence - Robert Walker; Marilyn Howard; Sue Maguire; Rachel Youngs (New Zealand Government, The Treasury, 2000)
This paper summarises the conclusions from a more extensive report commissioned by the Treasury and the Ministry of Social Policy to provide an explanation of growth in welfare benefit receipt in Britain in the period 1971 to 1997. The study is structured around a simple heuristic model of four sets of influences, 'drivers', the interaction of which helps to explain trends in claimant caseloads: the economy, demography, welfare institutions and belief systems. Four sets of claimants are considered: unemployed people, disabled people, retirement pensioners and children and families. It assembles a widely dispersed literature, in the first comprehensive review of the evidence on this issue. The conclusions reported here are supported in the full report by a wide range of data and analyses. The full report has been extensively edited, updated, reformatted and published in September 2000 by the Policy Press at the University of Bristol, under the title The Making of A Welfare Class? Benefit receipt in Britain, by Robert Walker with Marilyn Howard. Details of this publication may be obtained through the link to the Policy Press website: http://www.bris.ac.uk/Publications/TPP/catalog.htm The study concludes that, while caseloads increased across the four domains, they did so for very different reasons. While the process of de-industrialisation provided an important back-cloth to all the changes, it was only directly implicated as a major influence in the growth of unemployment related benefits. The upward trends in disability benefits were principally a reflection of the greater social awareness of the personal costs of disability, while the growth in benefits pertaining to the family was very largely a response to changing social attitudes and sexual behaviour. Demography, notably increased longevity, explains the observed growth in pensioner caseloads although the balance between contributory and means-tested pensions was the result of foresighted policy decisions made between the 1940s and 1970s.
Keywords: 330